Pengaruh Pelatihan, Motivasi, dan Tingkat Pendidikan Guru Terhadap Kinerja Guru SMK Negeri di Kabupaten Indragiri Hilir - Yuliani, Dona; Prasojo, Lantip Diat (Jayapangus Press, 2025)
This study aims to determine, (1) The Effect of Teacher Training on Teacher Performance. (2) The Effect of Teacher Motivation on Teacher Performance. (3) The Effect of Teacher Education Level on Teacher Performance. (4) The Effect of Training, Motivation and Education Level of Vocational High School Teachers on the Performance of State Vocational High Schools in Indragiri Hilir Regency. The study used a quantitative method with a quantitative approach and an ex-post facto method. Respondents in this study were state vocational high school teachers in Indragiri Hilir Regency, Riau Province with a sample of 163 teachers selected using proportional random sampling techniques from a total population of 274 state vocational high school teachers. The data collection technique used a questionnaire with a validity test using Pearson Product Moment correlation with Cronbach Alpha for reliability testing. The data analysis technique was carried out using a simple linear regression test and multiple linear regression tests and was supplemented with partial tests, simultaneous tests and coefficients of determination. The results of the study showed that, (1) The effect of teacher training on teacher performance was 11%. (2) The effect of motivation on teacher performance was 6.3% (3) The effect of teacher education level on teacher performance was 65%. (4) The influence of training, motivation and teacher education level on teacher performance is 58.1%. This explains that training, motivation, training and teacher education level have a significant influence on the performance of state vocational school teachers in Indragiri Hilir Regency.